Polarisasi etnis dan potensi konflik dalam kebijakan pencetakan sawah baru: Sebuah kajian kepustakaan - Dwi Wulan Pujiriyani (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
This study aims to analyse the implementation of new rice field plan policies in Indonesia and their impacts on population and ethnic composition in new rice field locations. This research is conducted by applying a literature review method. It is shown that the implementation of the policies had two major implications. Firstly, it creates assimilation opportunities through collaboration between ethnic migrants and local ethnic groups to work on or cultivate new rice fields. Secondly, the great flows of transmigrants that move to the new rice field locations trigger ethnic polarization, which is prone to cause inter-ethnic conflict. In the future, potential problems associated with the provision of new rice fields are available are the risk of having aging population. The aging population indicates a decrease in productive labor that may also affect on decreasing attractiveness of the rice fields to the younger generation. This situation can lead to the re-involvement of older generation in managing the new rice fields. However, it can raise a new concern on their ability to improve the rice fields’ productivity or, even worse, the new rice fields might be neglected or be sold.